Effect of estradiol with or without micronized progesterone on cholinergic-related cognitive performance in postmenopausal women - Conley, Alexander C.; Vega, Jennifer N.; Johnson, Julia V.; Dumas, Julie A.; Newhouse, Paul A. (Frontiers in Neuroscience, 2024)
Women are at a higher risk of developing Alzheimer's disease (AD), and the decline in estrogens post-menopause is thought of as a factor increasing this risk. Estradiol (E2) is important in supporting cholinergic neuronal integrity, and cholinergic functioning may be negatively impacted following the loss of E2 post-menopause. The use of exogenous E2 has been observed to enhance cholinergically mediated cognitive performance in healthy post-menopausal women, which indicates a potentially protective mechanism. However, E2 is often co-administered with progestin or progesterone to prevent endometrial proliferation. Progesterone/progestins have previously been shown to have a detrimental effect on E2-mediated biological and cognitive effects mediated by cholinergic systems in preclinical models, therefore the present study aimed to assess whether progesterone would modify the effect of E2 to influence cognition during cholinergic blockade. Twenty participants completed 3months of oral E2 treatment with micronized progesterone (mPRO) or with placebo (PLC) in a repeated-measures within-subjects crossover design, in which they also completed five anticholinergic challenge days per hormone treatment condition. During the challenge participants were administered low or high doses of the nicotinic cholinergic antagonist mecamylamine, the muscarinic cholinergic antagonist scopolamine, or placebo. Following drug administration participants performed cognitive tests sensitive to cholinergic tone, assessing attention, episodic memory, and working memory. Significant decrements were found on some tasks when participants were taking E2+mPRO compared to E2 alone. Specially Specifically, under more challenging task conditions and larger anticholinergic doses participants showed poorer performance on the Critical Flicker Fusion task, and the Stroop test, and more responded more conservatively on the N-back working memory task. Other tasks showed no differences between treatments under cholinergic blockade. The findings show that mPRO, when taken in concert with E2, was detrimental to effortful cognitive performance, in the presence of cholinergic blockade. These results are important for assessing the impact of combined postmenopausal hormone treatment on cognitive functionperformance that is , dependent on cholinergic functioning after menopause and the potential 46 of hormone treatment to impact the long-term risk for cognitive decline.